A Sociological Perspective on Emotion Work and Judging - Anleu, Sharyn L. Roach (Oñati Socio-Legal Series, 2019)
Judicial work requires judicial officers to manage their own emotions and related conduct, as well as to anticipate, interpret, respond to and manage emotions and behaviours of others, most visibly in the interaction order of the courtroom. A detailed, sociological analysis of judicial interview data reveals the ways judicial officers themselves understand, manage and use emotion in their everyday work. Judicial emotion work is more than a purely individual or personal enterprise. It operates in accordance with explicit and implicit feeling and display rules, cultural scripts and legal norms that shape the relation between emotion and judging. The ways judicial officers articulate their understanding of emotion in their everyday work reveals their reproduction and potential transformation of the boundaries between emotion and their status as judge. These findings reposition emotion work as central to judicial performance and enable emotion itself to be recognised as a positive judicial resource.